Why Indonesia Should Keep Joining in Trade and Investment Agreements? - Widiatedja, I Gusti Ngurah Parikesit; Wairocana, I Gusti Ngurah; Suyatna, I Nyoman (Faculty of Law, Hasanuddin University, 2019)
There have been some concerns over the existence of trade and investment agreements. They have been doubted because of the poverty and inequality issues in some regions across the globe. The rise of the spirit of national interest of their members has also exacerbated the situation. Hence, these two miserable facts may end up with a question whether Indonesia should keep joining trade and investment agreements. This article is aimed to examine if Indonesia should continue its participation in trade and investment agreements. Employing a normative legal research, this article put three parameters, analysing the continuity of Indonesia’s participation, namely the benefits of international trade and foreign direct investment, the rationale of trade and investment agreements, and how trade and investment agreements (that involve Indonesia) have positively affected Indonesia’s development. This article then claims that Indonesia should keep joining trade and investment agreements for realising its targets on economic growth and development.